Outcomes of non-high grade serous carcinoma after neoadjuvant chemotherapy for advanced-stage ovarian cancer: a Korean gynecologic oncology group study (OV 1708) - Young Shin Chung; Sang-Yoon Park; Jung-Yun Lee; Jeong-Yeol Park; Jeong-Won Lee; Hee Seung Kim; Dong Soo Suh; Yun Hwan Kim; Jong-Min Lee; Miseon Kim; Min Chul Choi; Seung-Hyuk Shim; et al. (BMC Cancer, 2019)
Abstract Background Outcomes of patients with ovarian high-grade serous carcinoma (HGSC) treated with neoadjuvant chemotherapy (NAC) have been widely studied, but there is limited information on the outcomes of patients with non-HGSC. This study aimed to evaluate the outcomes of NAC in non-HGSC patients with advanced-stage ovarian cancer. Methods We conducted a retrospective cohort study of patients who underwent NAC for advanced stage non-HGSC between 2002 and 2017 in 17 institutions. Demographics, surgical outcomes, and survival rates were evaluated according to histological subtypes. Results A total of 154 patients were included in this study, comprising 20 cases (13.0%) of mucinous adenocarcinoma, 31 cases (20.1%) of endometrioid adenocarcinoma, 28 (18.2%) cases of clear cell carcinoma, 29 (18.8%) cases of low-grade serous carcinoma and 12 cases (7.8%) of carcinosarcoma. Complete remission/partial remission after the third cycle of NAC was achieved in 100 (64.9%) patients and optimal debulking surgery (residual disease ≤1 cm) at interval debulking surgery was achieved in 103 (66.9%) patients. The most common reason for performing NAC was high tumor burden (n = 106, 68.8%). The median progression-free survival (PFS) was 14.3 months and median overall survival (OS) was 52.9 months. In multivariate analyses, mucinous and clear cell carcinoma were negative prognostic factors for both PFS (p = 0.007 and p = 0.017, respectively) and OS (p = 0.002 and p = 0.013, respectively). Conclusions In this study, poor survival outcomes were observed in patients with mucinous and clear cell carcinoma undergoing NAC. Different treatment strategies are urgently required to improve survival outcomes for this disease subset.